The Use of Person Deixis as Address System In Literary Works - Ummi Hanik; Oktiva Herry Chandra (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
Deixis is one of topics in Pragmatics that always be studied by researchers on their own reason. This research is a study of person deixis as address system within novel entitled Their Eyes Were Watching God from Zora Neale Hurston and story book Friday Black by Nana Kwame Adjei-Brenyah as the source of data in this study, which the author of each book is Black people. The purpose of analyzing, the writer would like to analyze the system address system in both sources and look for the address system from the sources. The data were collected by library research method. The collected data were identified, categorized, and analyzed. The writer analyzed the data by using Levinson’s theory as method of analyzing the source data. The finding of the research is from two literary works the type that appears frequently is first-person deixis such as I, Ah, Ah’m from Their Eyes Were Watching God and I from Friday Black. The person deixis as address system that use in term of formal and informal dialogue. The last is the factors that affected the address system in both literary works.Keywords: deixis; address system; black cultural background.